Structure and Orientation of the Mn(4)Ca Cluster in Plant Photosystem II Membranes Studied by Polarized Range-extended X-ray Absorption Spectroscopy() - Pushkar, Yulia (2006)
X-ray absorption spectroscopy has provided important insights into the structure and function of the Mn(4)Ca cluster in the oxygen-evolving complex of Photosystem II (PS II). The range of manganese extended x-ray absorption fine structure data collected from PSII until now has been, however, limited by the presence of iron in PS II. Using a crystal spectrometer with high energy resolution to detect solely the manganese Kα fluorescence, we are able to extend the extended x-ray absorption fine structure range beyond the onset of the iron absorption edge. This results in improvement in resolution of the manganese-backscatterer distances in PS II from 0.14 to 0.09 Å. The high resolution data obtained from oriented spinach PS II membranes in the S(1) state show that there are three di-µ-oxo-bridged manganese-manganese distances of ~2.7 and ~2.8 Å in a 2:1 ratio and that these three manganese-manganese vectors are aligned at an average orientation of ~60° relative to the membrane normal. Furthermore, we are able to observe the separation of the Fourier peaks corresponding to the ~3.2 Å manganese-manganese and the ~3.4 Å manganese-calcium interactions in oriented PS II samples and determine their orientation relative to the membrane normal. The average of the manganese-calcium vectors at ~3.4 Å is aligned along the membrane normal, while the ~3.2 Å manganese-manganese vector is oriented near the membrane plane. A comparison of this structural information with the proposed Mn(4)Ca cluster models based on spectroscopic and diffraction data provides input for refining and selecting among these models.